New record of a stahleckeriid dicynodont (Therapsida, Dicynodontia) from the Late Triassic of southern Brazil and biostratigraphic remarks on the Riograndia Assemblage Zone. (2nd November 2021) - Martinelli, Agustín G.; Escobar, Juan A.; Francischini, Heitor; Kerber, Leonardo; Müller, Rodrigo T.; Rubert, Rogerio; Schultz, Cesar L.; Da-Rosa, Átila. A. S.
ABSTRACT: Dicynodonts represent a speciose clade of non-mammalian synapsids that lived from the middle Permian to the Late Triassic, exhibiting a Pangaean distribution. The South American Norian fossil record is represented by two species: Jachaleria colorata from Argentina and J. candelariensis from Brazil. The Brazilian specimens come from a relatively small quarry located in the site known as Botucaraí or Botucaraí Hill (Candelária, Rio Grande do Sul). We describe here four dorsal vertebrae of a single individual referred to cf. Jachaleria candelariensis from a site named Alto Guarda Mor, located in the Faxinal do Soturno municipality, State of Rio Grande do Sul, Brazil. This taxonomic proposal and the lithological features of the site support that the outcrop belongs to the Riograndia Assemblage Zone (AZ; Candelária Sequence, Santa Maria Supersequence). Although the specimen cannot be referred unambiguously to Jachaleria candelariensis due to the lack of cranial material, it likely represents the second record of the genus in the Triassic of Brazil. We further discuss the faunal composition and relative age of some sites referred to the Riograndia AZ, which exhibit odd faunal context likely representing an AZ between the top of the Hyperodapedon AZ and the base of the Riograndia AZ.